Tessituras de um rio: deslocamentos de paisagens, memórias e ruínas - Heldilene Guerreiro Reale (2019)
The research presents the development of the artistic creation process started in July 2017, where I travel along an Amazon River between the Belém - Faro - Belém route, in the state of Pará. In order to investigate the memories established in the relationships built with the landscape and people present in this displacement, we sought to understand how travel memories and memories about the river participate in the landscape present in a process of artistic creation. The displacement in this river starts from affective memories that dialogue with this landscape for more than 20 years, and starts to be resignified as an artistic experience from this poetic process that developed visual and audiovisual productions that came into contact with the narratives of travelers, with the landscape and the ruins found in the city of Faro. The experience brings up issues that cross issues related to mining in the Amazon, environmental crimes, violence in the river, child labor and social problems, in addition to narratives that point out the presence of foreigners and their migratory processes. It also presents a reflection on ruin as an aspect of memory from the places of affection present in Faro. The creation process is present in the writing of a diary / work, on the travel map, in the records in drawings, photographs, audios and videos that formed the montage of the film “Tessitura de um Rio”, concluded after the exhibition held on the same path , in 2019. Navigation on this river is muddy, muddy, faces serious problems, but it is full of navigation that oscillates the permanence of rivers that touch intense confluences of memories.